Morphology and anatomy of the fruit and seed of Cananga odorata (Lam.) Hook.f. & Thomson - Ferawati Oktia Nurhayani; ARUM SEKAR WULANDARI; TATIEK KARTIKA SUHARSI (Society for Indonesian Biodiversity, 2019)
Abstract. Nurhayani FO, Wulandari AS, Suharsi TK. 2019. Morphology and anatomy of the fruit and seed of Cananga odorata (Lam.) Hook.f. & Thomson. Biodiversitas 20: 3199-3206. Cananga odorata (Lam.) Hook.f. & Thomson is one of the Annonaceae family which has high benefits for humans such as constructions, furniture, cosmetics, perfumes, and traditional medicines. The planting efforts were needed to support the existence of these plants. These plants have low regeneration and germination. The morphology and anatomy of fruit and seed could enhance the understanding of the reproductive biology in the species. There is little information about the morphology and anatomy of fruit and seed of C. odorata var. odorata forma genuina. The aim of this study is to understand the morphology and anatomy of fruit and seed of C. odorata. The morphologic description was made from the analysis of the fresh fruits and seeds. The anatomical description was made from the analysis of permanent slides with longitudinal sections of the fruits and seeds. The samples were fixed, dehydrated, alcoholized, embedding in paraffin, and stained with safranin-fast green. Data analysis consists of the morphological observation (shape, color, size and the number of seeds per fruits) and the anatomical observation (the pericarp layers of fruit, the seed coat layers, and the structure in the seed). The fruit of C. odorata var. odorata forma genuina was fleshy, ovoid or obovoid, 0.98-2.75 cm long, 0.42-1.63 cm in diameter, and contain 1-12 seeds. The seeds were pale brown, flattened, ovoid, and hard. The fruit anatomy showed that the pericarp layers derived from parenchymatous cells and differentiated into three zones, i.e. exocarp, mesocarp, and endocarp. The seed has ruminated endosperm with irregular folds. The seed coat was divided into three integuments, i.e. outer, middle, and inner integument. The information about the fruit and seed anatomy of C. odorata var. odorata forma genuina might enhance the understanding of future studies regarding natural reproduction and conservation programs with generative propagation.